The Palgrave Handbook of Urban Development Planning in Africa - Khayesi, Meleckidzedeck; Wegulo, Francis Nyongesa (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XVII, 376 p. 4 illus., 2 illus. in color.